MEDIA PANICS IBU RUMAH TANGGA SETELAH MENGAKSES BERITA COVID-19 - Setiyaningsih, Lian Agustina (Jurnal Nomosleca, 2020)
Abstract Media panics is an expression of panic in using media, it is a study of media effects. In the era of the corona pandemic, news about developments in social conditions, especially related to the increasing number of people who have contracted Covid-19 in Indonesia, has triggered panic media use. This study used a descriptive quantitative method by analyzing one variable, namely media panics of housewives after consuming news related to Covid-19. Respondents involved a number of 244 housewives in Indonesia. The sampling technique used was purposive sampling with descriptive analysis method. The results of this study prove that many housewives consume Covid-19 news, especially topics related to the increasing number of sufferers and the easy spread. This is caused by saturation of information, feeling disturbed, unable to avoid news, exposure and use of the media, and joining groups. whereas the factors that influence the unequal way of accepting the concept of modernity in media, cultural shocks of utilizing high-tech media, common habits, discourse panic Keywords: media panics, housewives, news, covid-19